2018
DOI: 10.1080/13548506.2018.1428757
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between demands for lung cancer screening and the constructs of health belief model: a cross-sectional survey in Hefei, China

Abstract: The aim of investigation is to explore the relationship between demands for lung cancer screening (LCS) and the constructs derived from the health belief model (HBM) in Hefei. The study collected data about socio-demographics, health beliefs in and demands for LCS during early June to later July 2015. By constructing a LCS demands HBM constructs, it calculated indices of demands for LCS (DSI) and HBM constructs, which include perceived risk (PR) and seriousness (PS) of the cancers; and perceived effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…One such avenue would be through the use of the Health Belief Model (HBM), which is used by researchers to better understand motivations to health-related behavior. [45][46][47][48] While the constructs of the HBM range from 4 to 6 which include, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, motivation and external cues to action, 49 the first 4 constructs are most often found in research. Perceived susceptibility addresses perceptions of the risk of acquiring a disease.…”
Section: Introductionmentioning
confidence: 99%
“…One such avenue would be through the use of the Health Belief Model (HBM), which is used by researchers to better understand motivations to health-related behavior. [45][46][47][48] While the constructs of the HBM range from 4 to 6 which include, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, motivation and external cues to action, 49 the first 4 constructs are most often found in research. Perceived susceptibility addresses perceptions of the risk of acquiring a disease.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth, perceived barriers, are the potential challenges with undertaking a recommended behavior. The HBM has been used in studies to explore behaviors related to chronic conditions [11] as well as health screening and health promotion [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, from 2010 to 2015, less than 5% of high-risk individuals (i.e., individuals who currently or formerly smoked long-term) had been screened [ 10 ]. From 2018 to 2019, the participation rate of high-risk individuals in lung cancer screening in China was only 6.4% to 31.91% [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that factors related to low screening rates in screening-eligible individuals include psychological and cognitive variables (e.g., stigma, mistrust, fatalism, worry, fear, and low knowledge levels related to lung cancer and lung cancer screening), health beliefs (perceived risk, perceived benefits, perceived barriers, and self-efficacy), healthcare provider recommendation, and social and media exposure [ 13 15 ]. Of these factors, health beliefs are an important predictor of lung cancer screening behavior [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%